FTIR spectra and conformations of 2'-deoxyuridine in Kr matrices: Classical Cryocrystals - Ivanov, A.Yu.; Karachevtsev, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The Fourier transform infrared spectra in the range 4000–200 см–1 of pyrimidine nucleoside 2'-deoxyuridine(dU) have been obtained in the low temperature inert Kr matrices. For the first time, instead of a usual flat mirror, a low temperature one-coordinate retroreflector was used as the matrix substrate. Owing to this, the matrix setup is insensitive to dip angle vibrations of the cryostat and is favourable to work with thinner matrix layers. Of two syn-conformers with dU_s1 and dU_s2 (stabilized by the intramolecular hydrogen bond O5'H…O2), only dT_s2 conformer with C2'-endo structure of the ribose ring was uniquely quenched. The height of the interconversion barrier of the minor syn-conformer dU_s1 was estimated to be below 0.7kcal/mole. It was shown that the energy relaxation of impurities in Kr is slower than in Ar matrices.